2000
DOI: 10.1177/000841740006700108
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Tool to Measure Clinical Competence in Occupational Therapy: A Pilot Study?

Abstract: Clinical competence is generally defined as a combination of knowledge, skill and professional behaviour. It is typically assessed using written tests, direct observation, chart audit, client satisfaction surveys and supervisor ratings. This paper describes the development and evaluation of a chart-stimulated recall (CSR) measure that combines the methods of chart audit and clinician interview to assess the clinical competence of practicing occupational therapists. The CSR tool was developed using the Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 30 publications
0
43
0
Order By: Relevance
“…18 Activities 1. Self-rated: perceived problematic skills (Canadian Occupational Performance Measure (COPM)), [19][20][21] and a semistructured interview of subjects and their partners (TE). 2.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…18 Activities 1. Self-rated: perceived problematic skills (Canadian Occupational Performance Measure (COPM)), [19][20][21] and a semistructured interview of subjects and their partners (TE). 2.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The possibility to perform these skills (0 ¼ major problems; 10 ¼ superior) and satisfaction with performance (0 ¼ major regrets; 10 ¼ extremely satisfied) were scored. 20 The performance and satisfaction scores were the average of the scores for the five skills. The reliability and validity of the instrument have been demonstrated in several disease populations.…”
Section: Activities: Self-ratedmentioning
confidence: 99%
“…Further, all of the assessors and 87% of the assessed physicians agreed that CBD was a useful quality improvement tool for revalidation. Salvatori et al (2000) reported a high correlation between supervisors' ratings and the CSR's interviewers' global ratings of overall competence of practicing occupational therapists denoting concurrent validity. The evidence supporting the use of CBD or CSR for the assessment of medical trainees emanated from subjective reports on their educational impact.…”
Section: Discussionmentioning
confidence: 94%
“…16,20 For example, the CPO's Practice Assessment also employs a chart-stimulated recall process. 40,41 Some study participants raised concerns about the accuracy of the materials included in the portfolio, noting that these can be susceptible to bias or inaccuracies. It has been suggested that cultural factors may influence both the way one presents oneself within portfolio records and the ease with which one keeps records.…”
Section: Discussionmentioning
confidence: 99%